2020
DOI: 10.1186/s12917-020-02560-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses induced by a combined vaccination with a recombinant chimera of Mycoplasma hyopneumoniae antigens and capsid virus-like particles of porcine circovirus type 2

Abstract: Background Mycoplasma hyopneumoniae (Mhp) and porcine circovirus type 2 (PCV2) are two important pathogens causing Mycoplasma pneumonia of swine (MPS) and porcine circovirus diseases and porcine circovirus-associated diseases (PCVDs/PCVADs), respectively, and resulted in considerable economic loss to the swine industry worldwide. Currently, vaccination is one of the main measures to control these two diseases; however, there are few combination vaccines that can prevent these two diseases. To determine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Freund’s adjuvant is an oil adjuvant widely used in animal vaccines, but its ability to stimulate the production of antibodies against recombinant protein is not good, and it often leads to excessive inflammatory responses [ 31 ]. Because of this, we used MontanideTM ISA 206 VG adjuvant in the piglet immunization experiments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Freund’s adjuvant is an oil adjuvant widely used in animal vaccines, but its ability to stimulate the production of antibodies against recombinant protein is not good, and it often leads to excessive inflammatory responses [ 31 ]. Because of this, we used MontanideTM ISA 206 VG adjuvant in the piglet immunization experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular docking results indicated that MhpMEVC6His could bind to immune-associated receptors, we performed animal immunization to validate our findings and studied the immune response. The design of the animal immunization was based on our previously published papers [ 31 , 66 , 67 ]. All animals (cleanliness of mice: SPF; cleanliness of piglets: free from Mhp and porcine circovirus type 2 infection) were kept in individually ventilated cages.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the development of combination vaccines has gradually become the main trend to adapt to the market's needs. 40 One important barrier for vaccination in countries with low and middle income is the current price of available vaccines. 41 The cost borne by combination vaccine recipients could be sufficient enough to be a hurdle for taking combination vaccines.…”
Section: Discussionmentioning
confidence: 99%